2020
DOI: 10.3390/s20041096
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Data Analytic Applications in Road Traffic Safety. Part 2: Prescriptive Modeling

Abstract: In the first part of the review, we observed that there exists a significant gap between the predictive and prescriptive models pertaining to crash risk prediction and minimization, respectively. In this part, we review and categorize the optimization/ prescriptive analytic models that focus on minimizing crash risk. Although the majority of works in this segment of the literature are related to the hazardous materials (hazmat) trucking problems, we show that (with some exceptions) many can also be utilized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The paper also reviewed the statistical and machine learning models used for crash risk modelling. Hu et al [3] categorized the optimization and prescriptive analytic models that focus on minimizing crash risk. Ziakopoulos et al [4] critically reviewed the existing literature on different spatial approaches that include dimension of space in its various aspects in their analyses for road safety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The paper also reviewed the statistical and machine learning models used for crash risk modelling. Hu et al [3] categorized the optimization and prescriptive analytic models that focus on minimizing crash risk. Ziakopoulos et al [4] critically reviewed the existing literature on different spatial approaches that include dimension of space in its various aspects in their analyses for road safety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gong [17,18] considered parameters such as materials, structure, traffic, and environment and successfully developed the Mechanistic-Empirical Pavement Design Guide (MEPDG) deep neural network model and GBM method for pavement rutting prediction, and the accuracy was improved. Hu [19] obtained risk indicators from a neural network prediction model and found that the application of data analysis improved the similarity of the predictive performance of the overall pavement safety level. Wang [20] et al proposed a training method to automatically determine the parameters of network structure for the deep belief network (DBN) with transfer learning (TL-GDBN).…”
Section: Introductionmentioning
confidence: 99%
“…The paper likewise evaluated the factual and AI models utilized for crash risk displaying. [3] classified the enhancement and prescriptive logical models that attention on limiting accident risk. Ziakopoulos.…”
Section: IImentioning
confidence: 99%